Sustainable Antibacterial Activity of Polyamide Fabrics Containing ZnO Nanoparticles - Garcia, Mariana Marin [UNESP]; Da Silva, Bruna Lallo [UNESP]; Sorrechia, Rodrigo [UNESP]; Pietro, Rosemeire Cristina Linhari Rodrigues [UNESP]; Chiavacci, Leila Aparecida [UNESP] (American Chemical Society (ACS), 2022)
In this study, we present an unprecedented study on the influence of parameters such as dyeing, softening, and number of washes on the maintenance of the antibacterial activity of polyamide fabrics containing zinc oxide nanoparticles (ZnO NPs) impregnated by a simple and easy-to-scale technique. ZnO NPs were synthesized by the sol-gel method at different reaction times (1, 3, and 24 h), followed by surface modification with (3-glycidyloxypropyl)trimethoxysilane (GPTMS) and water dispersion. The reaction times of ZnO NP synthesis were modified to evaluate their influence on particle size and antibacterial activity after impregnation in fabrics. The presence of ZnO NPs in fabrics was observed by different techniques such as X-ray diffraction, infrared vibrational spectroscopy, scanning electron microscopy, and energy-dispersive X-ray spectroscopy. The mean diameter values of the ZnO NPs calculated in this work from different techniques remained at 5 nm regardless of the reaction time revealing the efficient control of the nanoparticle size, important for desired applications as ZnO NPs smaller than 10 nm show improved antibacterial activity. The antibacterial activity of fabrics containing ZnO NPs indicated that polyamide fabrics after impregnation with ZnO NPs synthetized have great and similar biocidal potential against Staphylococcus aureus and Escherichia coli both with and without the presence of a fabric softener or a dye. The antibacterial behavior of the different polyamide fabrics remained after 10 and 20 washing cycles. The results shown in this study demonstrated the possibility of obtaining polyamide fabrics containing ZnO NPs with the antibacterial activity resistant to chemical treatments used by industries as a softener or a dye. The results also reveal the maintenance of the antimicrobial activity of fabrics after several washing cycles. The reaction time of 1 for the production of ZnO NPs and the versatility of polyamide fabrics allow their application in different environments to control microbial infections.
Keywords: antibacterial; fabrics; nanoparticles; polyamide; size; washes; zinc oxide